The Governor-General, the reserve powers, Parliament and MMP: A new era - Morris, Caroline (Victoria University of Wellington Law Review, 1995)
This article considers the reserve powers of the Governor-General to refuse a request for a dissolution of Parliament and to appoint a Prime Minister. Generally, these powers have not been the subject of much discussion or even considered to be of any great importance in constitutional debate. Yet the move to a mixed member proportional ("MMP") electoral system, endorsed by New Zealanders in a binding referendum in 1993, disturbs this previously settled consensus. MMP may mean that the reserve powers are called upon more often to solve constitutional dilemmas. Thus this article seeks to address the issues that arise from the new context for the operation of the reserve powers and further, to suggest some new conventions which may go some way towards the resolution of those issues.